The associations between relative and absolute body mass index with mortality rate based on predictions from stigma theory. (September 2022) - Pavela, Gregory; Yi, Nengjun; Mestre, Luis M.; Lartey, Stella; Xun, Pengcheng; Allison, David B.
Abstract: Background: The social consequences of obesity may influence health and mortality rate (MR), given obesity's status as a highly stigmatized condition. Hence, a high absolute body mass index (BMI) in conjunction with the stigmatization of a high BMI may each independently increase the rate of MR. Objectives: We tested whether relative BMI, defined as ordinal rank within a social reference group jointly defined by age, sex, and race/ethnicity, is associated with MR independent of absolute BMI. Methods: Data were from three nationally representative datasets: the Health and Retirement Study (n = 31, 115), the National Health Interview Survey (NHIS, n = 529, 362), and the National Health and Nutrition Examination Survey (n = 45, 033). Relative BMI kg/m 2 deciles were calculated within twenty-four subgroups jointly defined by age (6 levels), sex (2 levels), and race/ethnicity (4 levels). The association between ordinal rank BMI and MR was assessed using Cox survival generalized additive models in each dataset with adjustments for age, race, sex, smoking, educational attainment, and absolute BMI. Results: Absolute BMI had a significant non-monotonic association with MR, such that BMI was positively associated with mortality at BMI levels above approximately 25 kg/m 2 . Contrary to expectations, results from NHIS indicated that individuals in the first decile of relative BMI had the highest MR whereas relative BMI was not associated with MR in the NHANES and HRS. Conclusion: We hypothesized that the stigmatization of obesity might lead to an increased MR after controlling for absolute BMI. Contrary to expectations, a higher relative BMI was not associated with an increased MR independent of absolute BMI. Highlights: A higher absolute BMI is associated with a higher mortality rate independent of relative BMI within a socially defined reference group. A higher BMI relative to a socially defined reference group was not associated with mortality rate independent of absolute BMI. After adjusting for absolute and relative BMI, having less than a high school education and being a former or current smoker are significantly associated with a higher mortality rate.